He Term Poetry, Ancient And Modern - عبشي نزار; يعقوب لينا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research deals with the concept of poetry, in the past and present, and defined it in language and idiomatically. It reached a conclusion which is the disparity of critics in touching the parts of the form. Contemporary critics expanded on the picture; This is because poetry is linguistic units and changing and renewed relationships, full of constant newness, so that the image becomes a carrier of all contents, which opens to many connotations, the recipient contributes to uncovering its mysteries using his taste, culture, and his experience with the minutes of linguistic structures that formed the poetic painting. Based on the foregoing, we see the presence of indications that establish modern theories, including the psychological aspect that Ibn Qutaybah talked about through the times of poetry, and we find a role for the recipient in the concept of Ibn Rashiq al-Qayrawani, and we find important issues in the phonological analysis of Ibn Jinni who approached modern language schools . Therefore, returning to the heritage is a return to the ways of thinking of these scholars, and what they brought about, hoping that we will reach an Arab theory from the womb of this heritage. Because language does not stop at a specific time, it is developed and not static in molds. As such, the poetics of language stems from its own use, whereby the expressions of context create its poetry. Accordingly, the poetic text is an unknown, difficult world. Because it is based on the symbol, then he entered into the modern poetic image and the concept of the image in the dictionaries of language and modern literature theory, then he touched on al-Qadi al-Jarjani and Arabic poetry, and he dealt with the concept of poetry in the lexicon of the term, and the development of this concept among Arab critics, as he introduced the issues of the column of poetry, and waded in Pronunciation, meaning, typography, workmanship, weight, and rhetoric, as well as clarity and ambiguity, and then the research presented an applied aspect.